Prevalence and Antibiotic Resistance Pattern of Pathogenic Bacteria Isolated from Urinary Tract Infections in Hilla hospital, Iraq - Hamza, Zaman S. (International Journal of Scientific Research in Biological Sciences, 2023)
A laboratory received a referral of 740 patients who exhibited clinical signs of urinary tract infection (UTI). Out of the 240 urine culture samples that yielded positive results, 65.83% were obtained from female patients (n = 158), while 32.15% were obtained from male patients (n = 82). The chi-square test demonstrated a statistically significant correlation between being female and experiencing a urinary tract infection (P<0.05). Among the total samples, 206 samples (85.83%) were classified as gram-negative bacteria, whereas 34 samples (14.16%) were classified as gram-positive bacteria. The experiment involved obtaining samples of urinary tract infections (UTIs) to isolate the bacteria E. coli, P. mirabilis, E. aerogenesis, S. aureus, and E. faecalis. The prevalence rates of E. coli and P. mirabilis, which are gram-negative uropathogens, were 44.58% and 28.33% respectively. Staphylococcus aureus was the predominant gram-positive bacteria responsible for urinary tract infections, with a prevalence rate of 8.6%. Women exhibited a higher overall prevalence of bacteria compared to men. AK and GEN exhibited the highest efficacy against E. coli and P. mirabilis. AMC and TI displayed minimal efficacy against E. coli, but TMP and NIT revealed minimal activity against P. mirabilis. P. aerogenes had the most vulnerability to AK and NOR, while demonstrating the lowest susceptibility to AMC. In general, the antibiogram profiles revealed that AK and GEN had superior effectiveness in comparison to the other medications that were analysed. Enterococcus faecalis has exhibited resistance to amoxicillin-clavulanate (AMC), ampicillin (AMP), and doxycycline (DO), while vancomycin (VA) and linezolid (L) have demonstrated the highest efficacy as antibiotics. On the other hand, S. aureus showed the highest level of resistance to AMP, but the lowest level of resistance to VA and LEV.